Pengembangan Kurikulum Darurat Covid-19 (model dan media pembelajaran pada masa pandemi covid-19) - Mohamad Eri Hadiana; Erlita Octiana Nur’alimah (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
The existence of the corona virus outbreak has affected several sectors including the education sector. In dealing with the spread of the covid-19 virus, the government issued a distance learning policy with an emergency curriculum. The purpose of this study will discuss the models and learning media during the Covid-19 pandemic with library research sourced from research journals, the curriculum used at Al-Fatih Primary Islamic School and other literature that supports this research. The results showed that the emergency curriculum has high flexibility and provides space for educational institutions to develop the curriculum structure up to the evaluation stage. The models used during this pandemic were e-learning, blanded learning and home visits. The learning media used depend on the needs of teachers and students, including zoom, WhatsApp, and other media that can support learning online (online).